2022
DOI: 10.3389/fphys.2022.934163
|View full text |Cite
|
Sign up to set email alerts
|

Cold exposure and musculoskeletal conditions; A scoping review

Abstract: Background: Musculoskeletal conditions are major contributors to years lived with disability. Cold exposure can be a risk factor, but any conclusion is obscure.Aim: The aim of the present scoping review was to identify the existing evidence of an association between cold exposure and musculoskeletal conditions. The aim also included to consider pain in different regions and their assessment, as well as different measures of cold exposure, effect sizes, and to assess the feasibility of future systematic reviews… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 41 publications
2
8
0
Order By: Relevance
“…To conclude, the occurrence of upper extremity pain in our study was roughly in line with other recent investigations, although temporal data and more specific definitions of pain outcomes would have made comparisons easier. Our findings of statistical associations between contact and ambient cooling in relation to reporting upper extremity pain are also in line with the general trend of previous research ( 5 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…To conclude, the occurrence of upper extremity pain in our study was roughly in line with other recent investigations, although temporal data and more specific definitions of pain outcomes would have made comparisons easier. Our findings of statistical associations between contact and ambient cooling in relation to reporting upper extremity pain are also in line with the general trend of previous research ( 5 ).…”
Section: Discussionsupporting
confidence: 92%
“…In our study, any occurrence of upper extremity pain (regardless of location) was reported by 15%, which can be compared to official Swedish statistics, where roughly 19% reported work-related issues in the neck, shoulder and arm ( 19 ). In a recent scoping review, it was concluded that studies on the association between cold exposure and MSDs are heterogenous with regards to study samples, measures of exposure and outcome, as well as methodological approaches ( 5 ). However, the included studies generally indicated that cold exposure increases the risk of MSDs, and this was demonstrated separately for the hands and wrists ( 10 , 11 , 20 , 21 ), lower arms and elbows ( 11 , 20 , 21 ) as well as upper arms and shoulders ( 10 , 20 , 22 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a large body of occupational epidemiologic findings showing associations between NSP and LBP and several occupational ergonomic exposures, such as manual material handling, awkward body postures, repetitive movements, vibration, and high job demands (Ariens et al 2000;Marras 2000;Mayer et al 2012;Farioli et al 2014;Iqbal and Alghadir 2017;Kuijer et al 2018; Swedish agency for health technology assessment and assessment of social services 2022). However, it has been suggested that occupational cold exposure could be an additional risk factor for developing NSP and LBP (Pienimäki 2002;Mäkinen and Hassi 2009;Farbu et al 2021b, a).…”
Section: Introductionmentioning
confidence: 99%